Odpowiedź:
1)
2(a – 4)(3 + 2a) – 4(2 – 3a)(a – 3) –5a(2a – 4) dla a = -2
2(3a + 2a² - 12 - 8a) - 4(2a - 6 - 3a²+ 9a) =
= 2(2a²+ 11a - 12) - 4(-3a²+ 11a - 6) = 4a²+ 22a - 24 + 12a²- 44a + 24 =
= 16a²- 22a = 16 * (- 2)² - 22 * (- 2) = 16 * 4 + 44= 64 + 44 = 108
2)
–3(x – 4)(2 + x) + 3(2x – 1)(1 + 2x) – 4x(x – 2) dla x = -1.
-3(2x + x² - 8 - 4x) + 3( 2x + 4x² - 1 - 2x) - 4x² + 8x =
= - 3(x² - 2x - 8) + 3(4x² - 1) - 4x²+ 8x =
= - 3x² +6x + 24 + 12x² - 3 - 4x² + 8x = 5x² +14x + 21 =
= 5 * ( - 1)² + 14 * (- 1) + 21 =5 * 1 - 14 + 21 = 5 + 7 = 12